2022
DOI: 10.3390/su141912936
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Customer Repurchase Intention through Cognitive and Affective Experience: An Insight of Food Delivery Applications

Abstract: Mobile food order applications have become a phenomenal disruption in the food delivery industry. Customers demand better and more consistent experiences when making most purchases, including in food choices. Food delivery platforms have also been seen as the most convenient feature for customers during the global COVID-19 pandemic. Although food delivery applications have been widely used, there is only a scarce literature that focuses on the factors that optimize user experience and repurchase intention. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(130 reference statements)
0
1
1
Order By: Relevance
“…Female students were more likely to be OFD users. This is in contrast with some previous studies and market analyses ( 42 , 47 ), but our sample was skewed towards the female gender.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Female students were more likely to be OFD users. This is in contrast with some previous studies and market analyses ( 42 , 47 ), but our sample was skewed towards the female gender.…”
Section: Discussioncontrasting
confidence: 88%
“…On the other hand, older individuals could be less acquainted with new technologies, and they could be more prone to use conventional food ordering methods ( 23 , 41 ). Loyalty and personal affection as a customer are key elements for repurchase ( 23 , 42 ), and older people may not perceive some features of OFD services as affective elements, even if they are capable of positively influencing the customers experience (e.g., personalization, order customization and information availability) ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the clearer the user experience design, the greater the repurchase intent of Shopee application users. This study's findings are consistent with previous studies who found that user experience design has a positive effect on repurchase intention [38], [52].…”
Section: Regression Analysissupporting
confidence: 92%
“…Among the most prioritized were food apps, which offered unique user-friendly features and delivery options, such as intuitive search capabilities, easy sorting and navigation, convenient access to special offers, seamless payments, GPS-enabled systems, and 24/7 customer support (Khan et al, 2012). These features fostered greater interactivity between customers and the applications during COVID-19, as Riaz et al (2022) noted. The analysis results indicate that H1 shows a significant relationship, suggesting that the ease-of-use of mobile food apps significantly influences engagement with urban and semi-urban customers.…”
Section: Discussionmentioning
confidence: 99%